Financial evaluation of the establishment of a broiler processing plant in San Carlos, Alajuela, Costa Rica. - Montero Solís, Nataly (2019)
This case study focused on determining the profitability of the establishment of a broiler chicken processing plant in the San Carlos canton in the Alajuela province, Costa Rica. With an evaluation period of 10 years, such plant will be administered by a farmers’ association. The principal criteria for financial assessment are Net Present Value (NPV) and (Internal Return Rate) IRR for the scenarios of equity financing and debt financing, in which the decision of executing the project is taken. The cost of capital ratio was obtained by the Capital Asset Pricing Model (CAPM), adjusted to allow its application to Costa Rican capital enterprises. Additionally, a sensibility analysis was applied, determining that the direct variable cost is the most critical variable, because the project only sustains a rise of such variable of a 2,5% to output an NPV equal to cero. The results